The Fiscal Council and the Multiannual State Financial Plan for 2024–2027 - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
The study analyses the information on the Fiscal Council that is included in the multi-annual financial plan of the State for the period 2024–2027. The Author points out the scope of this information and the legal significance of this information. The article shows that the legal nature of the Multiannual State Financial Plan has the consequence that the legislature is not bound by it.